2020
DOI: 10.1002/anie.202005374
|View full text |Cite
|
Sign up to set email alerts
|

The Carbonyl⋅⋅⋅Tellurazole Chalcogen Bond as a Molecular Recognition Unit: From Model Studies to Supramolecular Organic Frameworks

Abstract: In the last years, chalcogen bonding, the noncovalent interaction involving chalcogen centers, has emerged as interesting alternative to the ubiquitous hydrogen bonding in many research areas. Here, we could show by means of high‐level quantum chemical calculations that the carbonyl⋅⋅⋅tellurazole chalcogen bond is at least as strong as conventional hydrogen bonds. Using the carbonyl⋅⋅⋅tellurazole binding motif, we were able to design complex supramolecular networks in solid phase starting from tellurazole‐subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 75 publications
0
43
0
7
Order By: Relevance
“…Analysis of Chalcogen Bonds using SAPT Calculations Our studies were focused on investigations of the nature of strong chalcogen bonds that exist primarily between tellurium-containing nitrogen heterocycles and different Lewis bases. [12,15,17,18,21,[30][31][32][33] Thelatter are for instance oxygen or nitrogen atoms of heterocycles or amides.Inthis study,we chose tellurium-containing aromatics as model compounds and calculated the dimers and their complexes with acetamide,t rimethylamine,t rimethylphosphine,t etrachloromethane and pyridine ( Figure 1). Forc omparison purposes the corresponding sulfur-a nd selenium-containing complexes were also investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of Chalcogen Bonds using SAPT Calculations Our studies were focused on investigations of the nature of strong chalcogen bonds that exist primarily between tellurium-containing nitrogen heterocycles and different Lewis bases. [12,15,17,18,21,[30][31][32][33] Thelatter are for instance oxygen or nitrogen atoms of heterocycles or amides.Inthis study,we chose tellurium-containing aromatics as model compounds and calculated the dimers and their complexes with acetamide,t rimethylamine,t rimethylphosphine,t etrachloromethane and pyridine ( Figure 1). Forc omparison purposes the corresponding sulfur-a nd selenium-containing complexes were also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[12,32] Furthermore,i tc ould be shown that the intermolecular interactions between the tellurium atoms of tellurazoles and the oxygen atom of an amide group result in the formation of supramolecular wires and organic framework in solid state. [33] Due to fundamental theoretical investigations the principle of chalcogen bonding has been understood in terms of strength and orientation. [14,34,35] Three essential components contribute to the strength of chalcogen bonds:e lectrostatics, orbital mixing (induction interactions) and dispersion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der Fokus unserer Studien lag auf der Untersuchung der Natur starker Chalkogenbindungen, die vornehmlich zwischen tellurhaltigen Stickstoff‐Heterocyclen und verschiedenen Lewis‐Basen existieren [12, 15, 17, 18, 21, 30–33] . Letztere sind beispielsweise Sauerstoff‐ oder Stickstoffatome von Heterocyclen oder Amiden.…”
Section: Ergebnisse Und Diskussionunclassified
“…Neben Isotellurazoloxiden und Tellurdiazolen werden neuerdings auch Tellurazole als vielversprechende Bausteine zum Aufbau starker Chalkogenbindungen verwendet [12, 32] . Es konnte gezeigt werden, dass die intermolekularen Wechselwirkungen zwischen dem Telluratom des Tellurazols und dem Sauerstoffatom einer Amidgruppe zur Bildung supramolekularer Drähte und organischer Gerüstverbindungen in fester Phase führen [33] …”
Section: Introductionunclassified